Efficacy of GWO Optimized PI and Lead-lag Controller for Design of UPFC based Supplementary Damping Controller - Narayan Nahak; Ranjan Kumar Mallick (IAES International Journal of Robotics and Automation (IJRA), 2017)
On line tuning of FACTS based damping controller is a vital decisive task in power system. In this regard two things need to be addressed, one is selection of a proper controller and another one is selection of a powerful optimization technique. In this work Grey Wolf Optimizer (GWO) technique is proposed to tune parameters of PI and lead lag controller based on UPFC to damp intra plant and inter area electromechanical oscillations with single and multi machine power system. A broad comparison has been performed with eigen value analysis between optimized PI and lead lag damping controller subject to different disturbances in power system. The recently revealed GWO, standard PSO and DE techniques are explicitly employed to tune UPFC based PI and lead-lag controller parameters. The system response predicts that performance of GWO is much better than PSO and DE techniques, and also lead lag controller is a better choice than PI controller pertaining to design of UPFC based damping controller.